2017
DOI: 10.1038/ncomms14179
|View full text |Cite
|
Sign up to set email alerts
|

Polymeric mechanical amplifiers of immune cytokine-mediated apoptosis

Abstract: Physical forces affect tumour growth, progression and metastasis. Here, we develop polymeric mechanical amplifiers that exploit in vitro and in vivo physical forces to increase immune cytokine-mediated tumour cell apoptosis. Mechanical amplifiers, consisting of biodegradable polymeric particles tethered to the tumour cell surface via polyethylene glycol linkers, increase the apoptotic effect of an immune cytokine on tumour cells under fluid shear exposure by as much as 50% compared with treatment under static … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 56 publications
0
23
0
Order By: Relevance
“…Beyond gene delivery, polymeric NPs have also been utilized to sensitize tumor cells to TRAIL-mediated apoptosis in the presence of physiological forces. 108 Recent work from our lab has indicated that, in addition to chemical sensitizers, tumor cells become sensitized to TRAIL-mediated apoptosis in the presence of mechanical forces. 109 Mechanical force in the form of fluid shear stress, mimicking shear forces of those in the microvasculature in vivo , enhanced cancer cell TRAIL-mediated apoptosis in vitro compared to similar treatments under static conditions.…”
Section: Polymeric Nanoparticlesmentioning
confidence: 99%
“…Beyond gene delivery, polymeric NPs have also been utilized to sensitize tumor cells to TRAIL-mediated apoptosis in the presence of physiological forces. 108 Recent work from our lab has indicated that, in addition to chemical sensitizers, tumor cells become sensitized to TRAIL-mediated apoptosis in the presence of mechanical forces. 109 Mechanical force in the form of fluid shear stress, mimicking shear forces of those in the microvasculature in vivo , enhanced cancer cell TRAIL-mediated apoptosis in vitro compared to similar treatments under static conditions.…”
Section: Polymeric Nanoparticlesmentioning
confidence: 99%
“…Flow patterns on surfaces grafted with complex (say brush-like) structures have attracted much attention in the past decades due to their pivotal roles in both engineering 1 , like fabrication of microfluidic and nanofluidic devices 2 – 4 , and biomedical applications 5 , 6 (e.g. drug delivery 7 and organ culture 8 ). A commonly studied example of a brush-like soft matter surface is a polymer brush surface - a surface composed of polymer chains end-grafted onto a solid substrate, and the polymer chains can be stretched away from the surface when high-speed flow passes by 9 .…”
Section: Introductionmentioning
confidence: 99%
“…Inspired by NK cell cytotoxic activity, liposomal systems functionalized with a cell adhesion receptor, E-selectin, and an immune cytokine, tumour necrosis factor-related apoptosis-inducing ligand (TRAIL, also known as TNFSF10), that binds to death receptors on cancer cells to trigger apoptosis 107 have been developed to tether to immune cells in the circulation 105 . In mice, this approach improved the circulation half-life of TRAIL, killed tumour cells in the bloodstream and prevented the spontaneous metastasis of prostate cancer 108 .…”
Section: Drug Deliverymentioning
confidence: 99%